Seasonal variations, speciation and possible sources of mercury in the snowpack of Zhadang glacier, Mt. Nyainqêntanglha, southern Tibetan Plateau - Huang, Jie; Kang, Shichang; Guo, Junming; Zhang, Qianggong; Xu, Jianzhong; Jenkins, Matt G.; Zhang, Guoshuai; Wang, Kang (Science of The Total Environment, 2012)
Ten snowpits were sampled at the Zhadang glacier during 2008 and 2011 to investigate the seasonal variations, speciation, and sources of mercury (Hg) in the southern Tibetan Plateau. In the 2008 snowpit, total Hg (HgT), particulate matter, most of major ions were found in higher concentrations during the non-monsoon season than in the monsoon season. Analysis of Hg speciation indicated that HgT in the 2011 snowpits was dominated by particulate-bound Hg (HgP). Most of particulate matter in the 2008 snowpit was dominated by fine particulates, indicating that the influx of particulate matter and HgP was probably occurring by long-range transportation via general atmospheric circulation. Analysis of dominant ion Ca2+ and alkaline pH values has suggested that the long-range transported HgP, originating from dust storm activities, may be the most important source for Hg in the Zhadang glacier snowpit during the non-monsoon season. Backward-trajectory analysis indicates the majority of the air masses arriving at the Zhandang glacier originated from the arid regions of northwestern India (e.g., Thar Desert), confirming that arid regions in central and southern Asia are likely the main sources of Hg being deposited in the Zhadang glacier snowpit. This study also suggests that ice core records from the Tibetan Plateau may be useful tools for interpreting long-term historical records of atmospheric Hg deposition, and reconstructing Hg biogeochemical cycling.